Management of Natural Resources, Sustainable Development and Ecological Hazards III 2011
DOI: 10.2495/rav110521
|View full text |Cite
|
Sign up to set email alerts
|

The influence of national culture on tourists’ behaviour towards environment

Abstract: Culture as an important element in tourism plays its role in the form of attraction for tourists as well as aspects which influence tourists' behaviour. Several crosscultural studies have been done to find the differences between tourists' behaviour regarding their culture. Although there is no comprehensive definition for culture in literature, Hofstede provided a well-known model which divided national culture into five dimensions. Power distance, individualism /collectivism, masculinity/femininity, uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…Second, societies with high MAS scores are driven by achievements, competition, and success, while those with a low score value life quality and happiness. Passengers from a country with a low MAS score have more leisure time, thus leading to a high tourist demand [53]. MAS is significantly and negatively correlated to air-passenger flows, with a coefficient of 0.033. us, air passengers prefer destinations with similar MAS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Second, societies with high MAS scores are driven by achievements, competition, and success, while those with a low score value life quality and happiness. Passengers from a country with a low MAS score have more leisure time, thus leading to a high tourist demand [53]. MAS is significantly and negatively correlated to air-passenger flows, with a coefficient of 0.033. us, air passengers prefer destinations with similar MAS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Filimonau et al , 2018; Filimonau and Perez, 2018; Li, 2012; Li and Lu, 2016). Second, earlier studies underpinned by Hofstede's model have shown strong influence of cultural values on key operational areas, in various disciplines such as marketing, consumer behaviour, consumer preference, brand choice and so on (Farahani and Mohamed, 2011; Koc, 2020; Reisinger and Crotts, 2010). To the best of our knowledge, no study has applied the Hofstede model to explore and understand trustworthiness of information and perceptions of safety akin to different migrant tourists in developing destination contexts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reason being that “uncertainty avoidance” plays an important role in understanding travelling risks, and more important than other cultural dimensions in predicting cross-cultural behaviour (Alcantara-Pilar et al , 2017; Crotts, 2004). The “power distance” dimension has been strongly associated with adherence to safety rules and regulations in the tourism sector (Farahani and Mohamed, 2011), and therefore would be relevant for achieving the specific objective of this study. Furthermore, we maintain that sense of safety and trust of tourism information about a destination could be assessed and understood first on the basis of the impact of the culture of the country of origin of the migrant visitors in a destination country.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations